Pelatihan Peningkatan Keterampilan Bahasa Inggris bagi Para Calon Imam Projo di Wisma Puruhita Klender, Keuskupan Agung Jakarta - Mutiarawati, Elisabeth Vita; Dema, Yosef (Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Efforts to Improve English Skills for Priest Candidates in Jakarta were undertaken to enhance English proficiency and communication skills of Diocesan Priest Candidates. Conducted from September to December 2021 at Wisma Puruhita Klender, East Jakarta, the program employs interactive language learning methodologies led by qualified language instructors from Kwik Kian Gie School of Business Jakarta. The curriculum integrates practical application through real-life scenarios, case studies, and field visits to pastoral settings. Evaluation mechanisms encompass periodic tests, quizzes, and feedback sessions to ensure a comprehensive assessment of language acquisition and practical communicative abilities. Anticipated outcomes include improved English proficiency, enhanced communication skills, increased cultural competence, and a positive impact on pastoral work. Recognizing challenges such as diverse language backgrounds and time constraints, the program proposes tailored language support and flexible scheduling options. The conclusion envisions a cohort of priest candidates equipped with the linguistic and communicative tools necessary for impactful pastoral engagement within their diverse congregations. This initiative aspires to contribute to the growth and connectivity within religious communities in Jakarta, fostering inclusive communication and deepening the bonds between diocesan priest candidates and peoples they serve.